Preparation of Naphthalene Dianhydride Bithiophene Copolymers by Direct Arylation Polycondensation and the Latent Pigment Approach. Issue 9 (12th June 2019) - Sanzone, Alessandro; Cimò, Simone; Mattiello, Sara; Ruffo, Riccardo; Facchinetti, Irene; Bonacchini, Giorgio E.; Caironi, Mario; Sassi, Mauro; Sommer, Michael; Beverina, Luca
Abstract: An alternating naphthalene dianhydride bithiophene copolymer (PNDAT2) is prepared by a combined direct arylation polycondensation and the latent pigment approach. PNDAT2 is the first reported example of an alternating conjugated polymer containing naphthalene dianhydride, the oxo‐analogue of naphthalene diimide often used in electron‐acceptor conjugated polymers. PNDAT2 is resistant to organic solvents and can be generated directly as film by thermal treatment of the soluble tetraester precursor PNTET2. PNDAT2 is characterized by a LUMO level of −3.9 eV, similar to that of established naphthalene diimide containing soluble copolymers. This route to insoluble electron acceptor copolymers by thermal cleavage of soluble precursors is an alternative to classical cross‐linking or orthogonal processing strategies. Abstract : Hidden talents : The combination of direct arylation polymerization and the latent pigment approach enables the synthesis of an n‐type naphthalene dianhydride bithiophene copolymer: PNDAT2. The material can be prepared in situ by thermal treatment of the soluble corresponding tetraester precursor PNTET2. The electrochemical LUMO of PNDAT2 is −3.9 eV, consistent with similar naphthalenedimide‐containing polymers.